Light-driven solid-state electrolyte membrane and integrated flexible light-assisted solid-state sodium metal battery based on light-driven solid-state electrolyte membrane

By introducing photo-driven heterojunction fillers and lignocellulose into the electrolyte membrane of photo-assisted solid-state sodium metal cells, combined with the designed photoelectrochemical storage positive electrode with energy level matching, the problem of insufficient ion conductivity and interface stability in solid-state cells is solved, and efficient sodium ion storage and excellent cycling performance are achieved.

CN119833728AActive Publication Date: 2025-04-15UNIV OF SCI & TECH OF CHINA
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510034862.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-15
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The existing photo-assisted solid-state sodium metal batteries have shortcomings in ionic conductivity and interface stability, and the matching and integrated design of the photoelectric positive electrode are not physically and chemically enough, affecting the sodium ion storage kinetics.

Method used

A photo-driven solid electrolyte membrane was developed to generate a powerful photogenerating electric field by introducing a composite heterojunction filler of copper oxide and indium oxide and a lignocellulose soft filler in polyethylene oxide, thereby increasing the ionic conductivity and sodium ion transfer number. At the same time, the photoelectrochemical storage positive electrode is designed based on the energy level matching principle to improve the compatibility of the electrolyte/positive electrode interface.

Benefits of technology

It significantly improves the ion conductivity and sodium ion transfer number of the solid electrolyte membrane, improves the sodium ion storage kinetics, achieves rapid sodium ion storage and excellent cycling performance, and improves the mechanical properties and long-term cycling stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833728A_ABST
    Figure CN119833728A_ABST
Patent Text Reader

Abstract

The invention provides a light-driven solid-state electrolyte membrane and an integrated flexible light-assisted solid-state sodium metal battery based on the light-driven solid-state electrolyte membrane, and belongs to the technical field of batteries, the battery comprises the light-driven solid-state electrolyte membrane and a photoelectrochemical storage positive electrode; the light-driven solid electrolyte membrane comprises polyoxyethylene, heterojunction filler, wood fiber soft filler and sodium salt, wherein the heterojunction filler is a composite material of copper oxide and indium oxide; the photoelectrochemical storage positive electrode comprises an indium selenium oxide film, titanium dioxide and sodium vanadium phosphate. According to the invention, trace heterojunctions are doped into polyethylene oxide electrolyte, and a photo-generated electric field generated by a photo-driving mechanism is utilized to reduce interface impedance, so that the ionic conductivity and sodium ion transfer number are effectively improved; a photoelectrochemical storage positive electrode with matched energy level is combined, so that a photon-generated carrier is utilized to the maximum extent, and the interfacial compatibility between the electrolyte and the positive electrode is enhanced; the battery assembled by the invention shows excellent cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a light-driven solid electrolyte membrane and an integrated flexible light-assisted solid-state sodium metal battery based thereon. Background Art

[0002] Light-assisted rechargeable sodium metal batteries have the advantages of high energy efficiency, lightweight structure and simplified design, which are crucial to the growing demand for portable electronics. However, addressing the intrinsic safety issues of liquid electrolytes and the sluggish reaction kinetics in existing photoelectrochemical storage cathodes remains a major challenge.

[0003] In order to overcome the inherent limitations of liquid-based light-assisted sodium metal batteries, recent research has turned to the development of light-assisted solid-state sodium metal batteries. Among them, polyethylene oxide-based composite solid electrolytes can effectively meet the required requirements due to their high flexibility, easy processing and good interface compatibility, but their low ionic conductivity and interface stability limit their further practical applications. Adding heterojunction fillers to polyethylene oxide can improve its low ionic conductivity. For example, Kang et al. prepared Bi4Ti3O 12 -BiOBr heterojunction filler is added to polyethylene oxide, and the ionic conductivity is improved (Adv. Funct. Mater. 2023, 33, 2307263. DOI: 10.1002 / adfm.202307263). However, this type of heterojunction filler does not have other functional properties such as photocatalysis to further improve the ionic conductivity, and it is still difficult to meet the actual use needs.

[0004] At the same time, although the light-assisted mechanism has been preliminarily applied in light-assisted solid-state sodium metal batteries, the photoelectric positive electrode still needs to be reasonably matched and integrated into an integrated design to better improve the sodium ion storage kinetics under the light-assisted mode, thereby achieving rapid sodium ion storage and excellent cycle performance. Summary of the invention

[0005] The present invention provides an integrated flexible light-assisted solid-state sodium metal battery based on the regulation mechanism of photocatalytically active heterojunction fillers developed based on the screening strategy, and combined with the coupled photoelectrochemical storage cathode. The present invention utilizes the heterojunction to generate a strong and stable photogenerated electric field driven by light, accelerates the dissociation of sodium salts, reduces the interface impedance, and thus effectively improves the ionic conductivity and the number of sodium ion transfers. At the same time, the solid electrolyte with optimized photoelectrochemical storage cathode pairing prepared based on the energy level matching principle can achieve high integration, improve the compatibility of the electrolyte / cathode interface, and significantly improve the sodium ion storage kinetics in the light-assisted mode, thereby achieving rapid sodium ion storage and excellent cycle performance.

[0006] The purpose of the present invention can be achieved by the following scheme:

[0007] The present invention firstly discloses a light-driven solid electrolyte membrane for a light-assisted solid-state sodium metal battery. The light-driven solid electrolyte membrane is prepared from polyethylene oxide, heterojunction filler, wood cellulose soft filler and sodium salt as raw materials.

[0008] Furthermore, the content of the heterojunction filler accounts for 1%-20% of the total mass of the solid electrolyte membrane, the content of the wood cellulose soft filler accounts for 0.5%-3% of the total mass of the solid electrolyte membrane, and the remainder is the polymer matrix material polyethylene oxide and sodium salt (molar ratio: [EO]: [Na] = 18:1).

[0009] Further, the heterojunction filler is a composite material of copper oxide and indium oxide, and its preparation method is: indium nitrate hexahydrate, copper nitrate trihydrate, 4,5-imidazole dicarboxylic acid and benzimidazole are added to dimethylformamide in a molar ratio of 0.08:0.034:0.512:(1.5-2.0) and ultrasonically stirred until dissolved. The resulting reaction mixture is heated to 90-120°C and maintained for 2-10 hours under continuous stirring, then centrifuged and dried, and then annealed at 400-600°C in a tube furnace filled with argon atmosphere to obtain the heterojunction filler. Most preferably: the reaction mixture is heated by an oil bath, the treatment temperature is 120°C, and the heating time is 4 hours. The annealing temperature is 500°C, kept for 1 hour and cooled naturally.

[0010] Furthermore, the sodium salt is sodium bis(trifluoromethane)sulfonyl imide (NaTFSI).

[0011] Furthermore, the thickness of the light-driven solid electrolyte membrane is 80-120 microns, preferably 100-105 microns.

[0012] Furthermore, the preparation method of the light-driven solid electrolyte membrane is: polyethylene oxide, heterojunction filler, wood cellulose soft filler and sodium salt are mixed in a solvent to obtain a membrane liquid, and then the light-driven solid electrolyte membrane is obtained by coating and drying. The specific steps are as follows:

[0013] (1) Dissolve polyethylene oxide and sodium salt in acetonitrile at the same time and stir evenly without generating bubbles.

[0014] (2) After the heterojunction filler and the wood cellulose soft filler are blended in acetonitrile, they are added to the solution of polyethylene oxide and sodium salt and stirred thoroughly to obtain a uniformly dispersed viscous membrane liquid; preferably, the mixture is stirred at room temperature for 6-20 hours.

[0015] (3) The membrane solution is evenly coated on a polytetrafluoroethylene plate, and vacuum dried for a period of time to obtain a light-driven solid electrolyte membrane. Preferably, the vacuum drying temperature is 50-70° C., and the drying time is 24-60 hours.

[0016] The present invention also discloses a photoelectrochemical storage positive electrode for a light-assisted solid-state sodium metal battery, which is prepared by uniformly coating titanium dioxide and sodium vanadium phosphate on the surface of an indium selenide oxide film in sequence and then drying. Preferably, the drying temperature is 60° C. and the drying time is 12 hours.

[0017] The present invention further provides an integrated flexible light-assisted solid-state sodium metal battery, which is assembled from a positive electrode, a negative electrode, a solid electrolyte membrane, a tab and a packaging film, wherein the positive electrode material is the above-mentioned photoelectrochemical storage positive electrode, the negative electrode is an ultra-thin sodium metal foil, the solid electrolyte membrane is the above-mentioned light-driven solid electrolyte membrane, and the packaging film is a transparent conductive film. Preferably, the packaging film is a light-transmitting indium selenide oxide film.

[0018] The preparation method of the integrated flexible light-assisted solid-state sodium metal battery can be: stacking a transparent conductive film, a positive electrode (pre-connected with a pole ear), a solid electrolyte membrane, a negative electrode (pre-connected with a pole ear) and a transparent conductive film in sequence, and packaging them with a battery sealing machine to obtain a transparent soft-pack battery.

[0019] The beneficial technical effects of the present invention are embodied in the following aspects:

[0020] 1. Compared with traditional polyethylene oxide electrolytes, the light-driven solid electrolyte membrane provided by the present invention can generate a strong and stable photoelectric field using a heterojunction under illumination conditions without additional external pressure, thereby improving electrolyte performance, reducing interface impedance, and effectively regulating the sodium salt dissociation and ion migration mechanism in the electrolyte, thereby effectively improving ionic conductivity and sodium ion transfer number.

[0021] 2. The light-driven solid electrolyte membrane provided by the present invention significantly improves the mechanical properties while maintaining high ionic conductivity by introducing an environmentally friendly, mechanically strong, sodium-compatible and resource-rich biomass resource - wood cellulose, thereby facilitating the construction of flexible solid-state batteries.

[0022] 3. Based on the energy level matching principle, the photoelectrochemical storage cathode provided by the present invention can achieve high integration, improve the compatibility of the electrolyte / cathode interface, and significantly improve the sodium ion storage kinetics in the light-assisted mode, thereby achieving rapid sodium ion storage and excellent cycle performance.

[0023] 4. The novel flexible light-assisted solid-state sodium metal battery carefully designed and assembled by the present invention exhibits excellent long-term cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a diagram of the mechanism of action of the light-driven solid electrolyte membrane of the present invention;

[0025] Figure 2 It is a schematic diagram of the energy level matching principle of the present invention;

[0026] Figure 3 is a schematic diagram of an integrated flexible light-assisted solid-state sodium metal battery of the present invention;

[0027] Figure 4 is the X-ray diffraction pattern of the heterojunction material prepared in Example 1 of the present invention;

[0028] Figure 5 is a scanning electron microscope image of the heterojunction material prepared in Example 1 of the present invention;

[0029] Figure 6 is a transmission electron microscope image of the heterojunction material prepared in Example 1 of the present invention;

[0030] Figure 7 is an X-ray diffraction pattern of the light-driven solid electrolyte membrane prepared in Example 1 of the present invention;

[0031] Figure 8 is a scanning electron microscope image of the light-driven solid electrolyte membrane prepared in Example 1 of the present invention;

[0032] Fig. 9 1 is an Arrhenius plot of the light-driven solid electrolyte membrane prepared in Example 1 of the present invention and the solid electrolyte membrane prepared in Comparative Example 1;

[0033] Fig.10 It is an infrared thermal imaging temperature change diagram corresponding to the light-driven solid electrolyte membrane prepared in Example 1 of the present invention and the assembled "perforated steel sheet||solid electrolyte membrane||perforated steel sheet" structure under the irradiation of a xenon lamp cold light source;

[0034] Fig.11 is a stress-strain test curve diagram of the light-driven solid electrolyte membrane prepared in Example 1 of the present invention and the solid electrolyte membrane prepared in Comparative Example 1;

[0035] Fig.12 is a graph of ion migration of the light-driven solid electrolyte membrane prepared in Example 1 of the present invention and the solid electrolyte membrane prepared in Comparative Example 1;

[0036] Fig.13 This is a schematic diagram of an integrated flexible light-assisted solid-state sodium metal battery prepared in Example 1 of the present invention lighting up an LED display screen;

[0037] Fig.14It is the cycle performance curve of the solid-state sodium metal battery prepared in Example 1 of the present invention and Comparative Example 1 under illumination and 0.2C current density.

[0038] Fig.15 This is the cycle performance curve of the solid-state sodium metal battery prepared in Example 1 of the present invention at a current density of 1C under illumination. DETAILED DESCRIPTION

[0039] In an embodiment of the present invention, an integrated flexible light-assisted solid-state sodium metal battery is provided, which is assembled from a light-driven solid electrolyte membrane, a photoelectrochemical storage positive electrode and a negative electrode. The light-driven solid electrolyte membrane is prepared by blending polyethylene oxide material, heterojunction filler, wood cellulose soft filler and sodium salt to obtain a membrane liquid, and then uniformly coating and drying. The heterojunction filler is a composite material of copper oxide and indium oxide. The mechanism of action of the light-driven solid electrolyte membrane in the present invention is as follows Figure 1 As shown in the figure: In the traditional polyethylene oxide solid polymer electrolyte, the strong O-Na+ coordination significantly hinders the migration of sodium ions, resulting in a low sodium ion transfer number. This problem can be improved by optimizing the coordination environment and enhancing the dissociation of sodium salts. Specifically, when irradiated with light, the photogenerated electric field of the active filler in the photocatalytic heterojunction weakens the O-Na+ + Coordination, thus significantly accelerating the dissociation of the sodium salt. After dissociation, the complexation of sodium ions with TFSI- must be suppressed to increase the availability of active sodium ions. The stable copper oxide has a narrow band gap. Indium oxide also has a narrow band gap, and the unique In 3+ The d10 electronic structure exhibits excellent visible light absorption, which is crucial for photocatalytic activity. Integrating copper oxide and indium oxide into a heterojunction structure can synergistically meet the requirements of light-driven modulation, thus providing a solid theoretical basis for the efficient dissociation of sodium salts.

[0040] The photoelectrochemical storage positive electrode designed according to the energy level matching principle in the embodiment of the present invention is prepared by uniformly coating titanium dioxide and sodium vanadium phosphate on the surface of the indium selenide oxide film in sequence and then drying it. Figure 2 As shown, reasonable energy level matching between indium tin oxide, titanium dioxide and sodium vanadium phosphate is utilized to effectively transfer photogenerated electrons and holes.

[0041] The embodiment of the present invention further provides an integrated flexible light-assisted solid-state sodium metal battery device, which is assembled from a positive electrode, a negative electrode, a solid electrolyte membrane, a tab and a packaging film, wherein the positive electrode material is a photoelectrochemical storage positive electrode, the negative electrode is an ultra-thin metal sodium foil, the solid electrolyte membrane is the above-mentioned light-driven solid electrolyte membrane, and the packaging film is a transparent conductive film. Preferably, a transparent indium tin oxide film is used as the packaging film to ensure light transmittance and flexibility. The structure of the integrated flexible light-assisted solid-state sodium metal battery device is as follows Figure 3shown.

[0042] The present invention is further described in detail below through specific examples.

[0043] Example 1

[0044] In this embodiment, a light-driven solid electrolyte membrane is first prepared, and then a photoelectrochemical storage cathode is prepared, and an integrated flexible light-assisted solid-state sodium metal battery device is further assembled based on the cathode. The specific operation steps are as follows:

[0045] 1. Dissolve 0.080mmol indium nitrate hexahydrate, 0.034mmol copper nitrate trihydrate, 0.512mmol 4,5-imidazoledicarboxylic acid and 1.692mmol benzimidazole in 16mL dimethylformamide. Stir the mixture using ultrasound for 10 minutes to ensure complete dissolution. Next, heat the reaction mixture to 120°C and maintain it for 4 hours under continuous stirring. After the reaction is complete, collect the product by centrifugation, wash it three times with distilled water and ethanol to remove any residual reactants, and dry it at 60°C for 24 hours. Then, grind the dried sample and heat treat it at 500°C in an argon atmosphere at a heating rate of 2°C per minute, maintain the temperature for 1 hour, and synthesize the heterojunction filler copper oxide / indium oxide. The X-ray diffraction pattern of the resulting heterojunction is shown as follows Figure 4 As shown in the scanning electron microscope image Figure 5 As shown in the transmission electron microscopy image Figure 6 shown.

[0046] 2. Sodium bis(trifluoromethane)sulfonyl imide (NaTFSI) and polyethylene oxide are added to anhydrous acetonitrile, and the molar ratio of ethylene oxide [EO] to [Na] is fixed at 18:1. Then, stir thoroughly until completely dissolved and no bubbles are generated. Disperse copper oxide / indium oxide in the electrolyte membrane at a mass fraction of 5% and wood cellulose in the electrolyte membrane at a mass fraction of 2%, and then stir thoroughly until completely dissolved, until the bubbles disappear, and obtain a uniform membrane liquid.

[0047] 3. The above film solution was applied to a polytetrafluoroethylene plate and a film was drawn using a film drawer, followed by vacuum drying at 60°C for 48 hours to obtain a light-driven regulated heterojunction solid electrolyte membrane (thickness of 100 μm), the X-ray diffraction pattern of which is as follows: Figure 7 As shown in the scanning electron microscope image Figure 8 shown.

[0048] 4. Dissolve 0.3g of titanium dioxide powder in 3mL of N-methylpyrrolidone, stir for 6 hours, evenly coat it on the surface of the indium selenide oxide film, and dry it at 60°C for 12 hours. Then, sodium vanadium phosphate, conductive carbon black and polyvinylidene fluoride binder with a mass ratio of 8:1:1 are mixed in the N-methylpyrrolidone solution to form a uniform slurry. Use a 200-micron film stretching preparation device to evenly coat it on the surface of the indium selenide oxide film, vacuum dry it at 60°C overnight, and obtain a photoelectrochemical storage positive electrode.

[0049] 5. Cut the purchased indium selenide oxide film with a thickness of 0.125 mm and a square resistance of 5 ohms into a size of 5.5 cm×3.5 cm, then ultrasonically clean it with detergent, deionized water, ethanol and acetone in sequence, and vacuum dry it.

[0050] 6. In a glove box filled with argon, the ultra-thin sodium foil, the light-excited regulated heterojunction solid electrolyte membrane and the photoelectrochemical storage positive electrode (pre-punched) are stacked in sequence, and then packaged with indium tin oxide film on a battery packaging machine, and the integrated flexible light-assisted solid-state sodium metal battery is assembled.

[0051] Comparative Example 1

[0052] Polyethylene oxide and NaTFSI were added to anhydrous acetonitrile, and the ratio of ethylene oxide [EO] to [Na] was fixed at 18:1. Stir thoroughly until it was completely dissolved and no bubbles were generated. Then, the mixed slurry was coated on a polytetrafluoroethylene plate and film-drawn with a film-drawing machine, followed by drying at 60°C for 48 hours to obtain a polyethylene oxide solid electrolyte membrane (thickness of ~85 microns).

[0053] The electrolyte membrane obtained in this embodiment is assembled into a solid-state sodium metal battery by using the same positive electrode, negative electrode and indium selenide oxide thin film as in Example 1 and in the same manner as in Example 1.

[0054] The solid electrolyte membranes obtained in the above embodiments and comparative examples were subjected to the following performance tests:

[0055] 1. Ionic conductivity: Assemble the “perforated steel sheet||solid electrolyte membrane||perforated steel sheet” structure, use a perforated battery shell (CR2032, 5 mm perforation diameter, CROOD Co., Ltd.) for packaging, and use a xenon lamp cold light source to simulate light irradiation from the perforation to illuminate the solid electrolyte membrane, test the bulk impedance R at different temperatures, and calculate the ionic conductivity σ at different temperatures according to the formula σ=l / RS, where l is the thickness of the film, R is the bulk impedance value, and S is the area of ​​the film.

[0056] Test results such as Fig. 9As shown: the solid electrolyte membrane prepared in Comparative Example 1 has no response to light, and its ionic conductivity at 40°C is 0.04 mS / cm; the solid electrolyte membrane prepared in Example 1 has an ionic conductivity of 0.067 mS / cm at 40°C in the absence of light, and an ionic conductivity of 0.101 mS / cm at 40°C in the presence of light.

[0057] In order to eliminate the influence of temperature, the light-driven solid electrolyte membrane prepared in Example 1 and the assembled "perforated steel sheet||solid electrolyte membrane||perforated steel sheet" structure were irradiated by a xenon lamp cold light source, and the temperature was monitored in real time using an infrared thermal imaging camera. Fig.10 As shown, it is confirmed that the light source does not affect the battery temperature.

[0058] 2. Stress-strain test: The electrolyte membrane is prepared as a 3cm×6cm sample. A tensile test machine is used to apply a gradually increasing tensile load to the membrane to cause deformation until it is destroyed. The maximum tensile stress required for the sample to fail is the stress yield strength.

[0059] Test results such as Fig.11 As shown, by comparing Example 1 and Comparative Example 1, it can be seen that the solid electrolyte membrane provided by the present invention, by adding wood cellulose and heterojunction filler to polyethylene oxide, has a stress strength that is 1.65 times that of Comparative Example 1 (the stress yield strength of the solid electrolyte membrane obtained in Example 1 is 6.37 MPa, and the stress yield strength of the solid electrolyte membrane obtained in Comparative Example 1 is 3.85 MPa), indicating that the solid electrolyte membrane provided by the present invention has good mechanical properties.

[0060] 3. Ion migration number detection: Assemble a symmetrical battery with the structure of "open-pore sodium||solid electrolyte membrane||open-pore sodium", and clamp the two sides with open-pore steel sheets, and use an open-pore battery shell (CR2032, opening diameter 5 mm, CROOD Co., Ltd.) for packaging. The opening positions of the sodium steel sheet and the battery shell are consistent to ensure that the light source can irradiate the solid electrolyte membrane. Place it on an electrochemical workstation for testing, and use a xenon lamp cold light source to irradiate the solid electrolyte membrane from the opening. Fig.12 As shown, the results show that the ion migration number of the solid electrolyte membrane obtained in Example 1 at 40°C is 0.42 under no light conditions and 0.49 under light conditions; the solid electrolyte membrane obtained in Comparative Example 1 has no response to light, and its ion migration number at 40°C is 0.17.

[0061] 4. Cycle number detection: Place the integrated flexible light-assisted solid-state sodium metal battery assembled in the above embodiment and the comparative example on the Xinwei test software, set the charge and discharge rate, cut-off voltage and other test conditions and start the test. At the same time, irradiate the solid electrolyte membrane through the punched position of the photoelectrochemical storage positive electrode through a xenon lamp cold light source or natural light, and wait for the cycle.

[0062] Under the irradiation of xenon lamp cold light source, Fig.13 As shown, the soft-pack battery assembled with the photoelectrochemical storage positive electrode in Example 1 successfully powered the LED while maintaining stable performance under bending conditions.

[0063] The electrochemical cycle performance curves of the solid-state sodium metal battery prepared in Example 1 and Comparative Example 1 under illumination and 0.2C current density are as follows: Fig.14 As shown. At a current density of 0.2C, the initial discharge capacity of the soft-pack battery assembled in Example 1 is 122.5mAh / g, the capacity retention rate after 125 cycles is 98.3%, and the energy storage efficiency is as high as 98.2%. However, the initial discharge capacity of the soft-pack battery assembled in Comparative Example 1 is 101.6mAh / g at a current density of 0.2C, showing poor cycle stability.

[0064] The cycle performance curve of the solid-state sodium metal battery prepared in Example 1 at a current density of 1C under illumination is as follows: Fig.15 At a current density of 1C, the initial discharge capacity of the soft-pack battery assembled in Example 1 is 132 mAh / g, the capacity retention rate after 300 cycles is 89.1%, and the energy storage efficiency is as high as 96.8%.

[0065] In summary, the integrated flexible light-assisted solid-state sodium metal battery benefits from the modification of the heterojunction solid electrolyte membrane and the photoelectrochemical storage cathode by light excitation regulation, and obtains high ionic conductivity, excellent electrochemical stability, mechanical strength and dendrite resistance. The rational design of the coupled photoelectrochemical storage cathode based on energy level matching effectively utilizes visible light and increases the strong compatibility between the electrolyte and the cathode, so that the integrated flexible light-assisted solid-state sodium metal battery achieves long cycle stability.

[0066] It will be easily understood by those skilled in the art that the above embodiments are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A light-driven solid electrolyte membrane for a light-assisted solid-state sodium metal battery, characterized in that: The light-driven solid electrolyte membrane is prepared from polyethylene oxide, heterojunction filler, wood cellulose soft filler and sodium salt as raw materials.

2. The light-driven solid electrolyte membrane according to claim 1, characterized in that: The heterojunction filler is a composite material of copper oxide and indium oxide.

3. The light-driven solid electrolyte membrane according to claim 1 or 2, characterized in that: The preparation method of the heterojunction filler is as follows: indium nitrate hexahydrate, copper nitrate trihydrate, 4,5-imidazoledicarboxylic acid and benzimidazole are added into dimethylformamide in a molar ratio of 0.08:0.034:0.512:1.5-2.0 and ultrasonically stirred until dissolved; the obtained reaction mixture is heated to 90-120°C and maintained for 2-10 hours under continuous stirring, then centrifuged and dried, and then annealed at 400-600°C in a tubular furnace filled with argon atmosphere to obtain the heterojunction filler.

4. The light-driven solid electrolyte membrane according to claim 1 or 2, characterized in that: The content of the heterojunction filler accounts for 1%-20% of the total mass of the solid electrolyte membrane, and the content of the wood cellulose soft filler accounts for 0.5%-3% of the total mass of the solid electrolyte membrane.

5. The light-driven solid electrolyte membrane according to claim 1 or 2, characterized in that: The thickness of the light-driven solid electrolyte membrane is 80-120 microns.

6. A method for preparing a light-driven solid electrolyte membrane according to any one of claims 1 to 5, characterized in that: Polyethylene oxide, heterojunction filler, wood cellulose soft filler and sodium salt are mixed in a solvent to prepare a membrane liquid, and then the light-driven solid electrolyte membrane is prepared by coating and drying.

7. A photoelectrochemical storage cathode for a light-assisted solid-state sodium metal battery, characterized in that: The photoelectrochemical storage positive electrode is prepared by uniformly coating titanium dioxide and sodium vanadium phosphate on the surface of an indium selenium oxide film in sequence and then drying the film.

8. An integrated flexible light-assisted solid-state sodium metal battery, characterized in that: The integrated flexible light-assisted solid-state sodium metal battery comprises the light-driven solid-state electrolyte membrane described in any one of claims 1 to 5, and also includes the photoelectrochemical storage positive electrode described in claim 7.

9. The integrated flexible light-assisted solid-state sodium metal battery according to claim 8, characterized in that: It is assembled from a photoelectrochemical storage positive electrode, a sodium metal negative electrode, a light-driven solid electrolyte membrane, a pole ear and a packaging film.

10. The integrated flexible light-assisted solid-state sodium metal battery according to claim 9, characterized in that: The packaging film is a transparent conductive film.

Citation Information

Patent Citations

  • Porous CuO / In2O3 dodecahedron compound and preparation method thereof

    CN110655103A

  • Heterostructure solid electrolyte membrane and all-solid-state battery

    CN115117424A

  • Integrated light-assisted secondary battery

    CN118782871A

  • Optical excitation regulation heterojunction solid electrolyte membrane and preparation method thereof

    CN118970170A

  • Photo-assisted catalytic composite sodium supplement, preparation method and sodium ion battery

    CN119944120A